HUBUNGAN ANTARA SUDUT PEMAKUAN DAN BEBAN TEKAN AKSIAL SEJAJAR SERAT PADA SAMBUNGAN BERHIMPIT PAPAN KAYU - Mursid Mufti; Putera Agung M. Agung (Jurnal Poli-Teknologi, 2013)
Relationship between angle of nailing direction and axial force in line with wood fibre has not been discussed yet indetail of “peraturan konstruksi kayu untuk indonesia (pkki), ni-5, 1961, in all section 15”, which explaines about wood joints with standard nailing. Nail material is one of joint instrument types which are used largely in wood construction. Research uses model test where variation of angle of nailing direction is apllied in one type of wood lap joint, and loads variation in loading test is accounted by amount of fabricated brickwall causing rupture of wood lap joint tested. The research shows that angle of nailing direction in range 60 – 140o would result maximum axial force in line with wood fibre. Keywords: angle of nailing direction, axial force